Editor's Choice – ECAR (Endovasculaire ou Chirurgie dans les Anévrysmes aorto-iliaques Rompus): A French Randomized Controlled Trial of Endovascular Versus Open Surgical Repair of Ruptured Aorto-iliac Aneurysms. Issue 3 (September 2015) - Desgranges, P.; Kobeiter, H.; Katsahian, S.; Bouffi, M.; Gouny, P.; Favre, J.-P.; Alsac, J.M.; Sobocinski, J.; Julia, P.; Alimi, Y.; Steinmetz, E.; Haulon, S.; et al.
Abstract : Objectives/Background: ECAR (Endovasculaire ou Chirurgie dans les Anévrysmes aorto-iliaques Rompus) is a prospective multicentre randomized controlled trial including consecutive patients with ruptured aorto-iliac aneurysms (rAIA) eligible for treatment by either endovascular (EVAR) or open surgical repair (OSR). Inclusion criteria were hemodynamic stability and computed tomography scan demonstrating aorto-iliac rupture. Methods: Randomization was done by week, synchronously in all centers. The primary end point was 30 day mortality. Secondary end points were post-operative morbidity, length of stay in the intensive care unit (ICU), amount of blood transfused (units) and 6 month mortality. Results: From January 2008 to January 2013, 107 patients (97 men, 10 women; median age 74.4 years) were enrolled in 14 centers: 56 (52.3%) in the EVAR group and 51 (47.7%) in the OSR group. The groups were similar in terms of age, sex, consciousness, systolic blood pressure, Hardman index, IGSII score, type of rupture, use of endoclamping balloon, and levels of troponin, creatinine, and hemoglobin. Delay to treatment was higher in the EVAR group (2.9 vs. 1.3 hours; p  < .005). Mortality at 30 days and 1 year were not different between the groups (18% in the EVAR group vs. 24% in the OSR group at 30 days, and 30% vs. 35%, respectively, at 1 year). Total respiratory support time was lower in the EVAR group than in the OSR group (59.3 hours vs. 180.3 hours; p  = .007), as were pulmonary complications (15.4% vs. 41.5%, respectively; p  = .050), total blood transfusion (6.8 vs. 10.9, respectively; p  = .020), and duration of ICU stay (7 days vs. 11.9 days, respectively; p  = .010). Conclusion: In this study, EVAR was found to be equal to OSR in terms of 30 day and 1 year mortality. However, EVAR was associated with less severe complications and less consumption of hospital resources than OSR.